2023
DOI: 10.13057/biodiv/d240219
|View full text |Cite
|
Sign up to set email alerts
|

Mapping coral cover using Sentinel-2A in Karimunjawa, Indonesia

Abstract: Abstract. Satya ED, Sabdono A, Wijayanti DP, Helmi M, Widiaratih R. 2023. Mapping coral cover using Sentinel-2A in Karimunjawa, Indonesia. Biodiversitas 24: 827-836. Coral reefs in the Karimunjawa National Park (KNP) have their own charm, especially for snorkeling and divers, it can be seen from the number of tourist visits which tends to increase every year, except for 2020 to 2021 due to the COVID-19 pandemic. This study aims to determine the impact of tourism on coral reef cover in KNP, with islands selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Analyzing the effect of ship tracking, several islands were selected that represented the level of tourist visits which were divided into the high, medium, and low levels. Data on tourist visits comes from the Indonesian Tourist Guide Association (Himpunan Pramuwisata Indonesia/HPI) which recorded visitors daily from November 2018 -March 2020 which was compiled and processed by [20] and is depicted in Figure 1. Using the approach of the more visitors come, the more ships are used, so the level of ship use is represented by the number of tourists visiting.…”
Section: Methodsmentioning
confidence: 99%
“…Analyzing the effect of ship tracking, several islands were selected that represented the level of tourist visits which were divided into the high, medium, and low levels. Data on tourist visits comes from the Indonesian Tourist Guide Association (Himpunan Pramuwisata Indonesia/HPI) which recorded visitors daily from November 2018 -March 2020 which was compiled and processed by [20] and is depicted in Figure 1. Using the approach of the more visitors come, the more ships are used, so the level of ship use is represented by the number of tourists visiting.…”
Section: Methodsmentioning
confidence: 99%
“…This finding begs the question whether the shift of the coral recruit density might be influenced by tourism activities and coral bleaching event. Several studies have reported that direct contact of tourist such as stepping, and standing on coral reef had negative impact by damaging coral reef ecosystem especially in the shallow area (Aldyan et al 2023;Wijaya et al 2021;Satya et al 2023) In the context of the impact of tourism activities, according to a study which assessed the coral damage in year 2016, coral damage was significantly higher in 2016 compared to 2020, when tourism was closed due to the pandemic (Rimayanti et al 2020). Meanwhile, in 2016, el Nino event in the Pacific Ocean, could affect the Karimunjawa and Kemujan islands.…”
Section: Coral Recruit Densitymentioning
confidence: 99%
“…Consequently, it is known as the Paradise of Java, or Caribbean van Java (Himawan & Lestari, 2016). Many local and foreigner around 3000-6000 visitors per month come to relish snorkeling and diving to explore the diversity of coral reefs (Satya et al, 2023). There is a demand for visitors coming to KNP that tends to increase every year.…”
Section: Introductionmentioning
confidence: 99%